Periodontal Disease in Dogs: Incidence and Comparative Efficacy of Ozonated Water versus Demineralized Water in Dental Scaling - K Patel, Abhishek; S Bhalodi, Apeksha; kumar J Mayani, Ankush; kumar V Parikh , Pinesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A retrospective study of 6,141 canine cases presented to the Veterinary Clinical Complex, Kamdhenu University, Anand (August 2023  to July 2024), identified 87 (1.42%) cases with oral affections. Of these, 21 (24.13%) were diagnosed with periodontal disease. Higher  incidence was noted in male and older dogs, the most affected breeds being Labrador Retrievers, German Shepherds, and Pomeranian  Spitz. Dogs on soft or vegetarian diets without oral hygiene showed increased susceptibility. Clinically, halitosis, abnormal salivation,  dental plaque, and calculus were the predominant findings. In a therapeutic trial with 14 affected dogs, two groups of seven received  ultrasonic dental scaling with either ozonated or demineralized water. Gram-positive cocci were the predominant isolates from dental  swabs, and Amikacin showed the highest antibiotic sensitivity (71.42%). Scaling with ozonated water reduced bacterial load significantly  (from 74.14 ± 8.13 ×10³ to 32.57 ± 4.77 ×10³ CFU/mL; p = 0.001), whereas demineralized water produced no significant change (79.86  ± 8.43 ×10³ to 70.00 ± 7.61 ×10³ CFU/mL; p = 0.064). These findings underscore the high incidence of periodontal disease in specific  canine demographics and demonstrate the superior antibacterial efficacy of ozonated water in canine periodontal disease management  through dental scaling. These findings suggest that ozonated water is more effective for bacterial control in periodontal lesions.
Keywords: Bacterial load; Canine; Dental scaling; Incidence; Ozonated water; Periodontal disease